PEDULI program: The method to increase women's environmental knowledge - Meydisa Utami Tanau; Sukma Noor Akbar; Rusdi Rusli; Silvia Kristanti Tri Febriana; Halimatus Sa'diyah; Marissa Mutia Rafika; Muhammad Rais Wildan; Natalia Mariana Advensya Natadjaja (Community Empowerment, 2023)
This community service aims to increase environmental knowledge of women through waste management training that targets cognitive, affective and conative. The methods used in this service are screening short films, Islamic religious lectures, training (making eco-enzymes, processing food waste, & waste management), and games. The service is carried out in 6 sessions (duration 420 minutes). The results of the analysis (T test) showed a significant difference between the pre-test scores (M = 56.2917, SD = 7.57845) and post-test scores (M = 61.3333, SD = 7.31090), t = - 3.986, p<0.05. This means that there is an increase in cognitive activity in participants and the PEDULI program has been effective for the sample group (housewives) through increasing knowledge and experience in increasing environmental awareness.